Disentangling Frictions Across the World: Markups Versus Trade Costs - Benedikt Heid; Frank Stähler (CESifo GmbH, 2024)
We develop a structural framework that allows us to quantify the evolution of aggregate bilateral trade costs and markups over time. With minimal assumptions, we can disentangle aggregate markup and trade cost changes from observed changes in trade flows. We apply our method to trade data between 1990 and 2015 for the world's 100 largest economies. We find that across all country pairs, on average, bilateral aggregate markups have increased by 2.8% per year. As bilateral trade costs have fallen by 3.1% per year on average, we find a strong negative correlation between observed trade cost and markup changes. Markups have increased less in high-income countries than in other countries.
Keywords: F10; F12; F14; F62; L13; 330; markups; trade costs; gravity; imperfect competition; market power